Level of Big Five Personality Factor among Players of Adapted Team and individual Sports - Haifa Saleh; Hasan Al Oran; Harran Al-Rahamneh (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: The study aims to assess the level of the big five personality factors (neuroticism, extraversion, agreeableness, conscientiousness and openness to experience) among players of adapted team and individual sports. It also assesses whether these factors are affected by type of game or experience. Methods: A descriptive approach was employed. The scale of the big five personality factors constructed by Costa and MacCrea (1989) was translated to Arabic. Content validity and internal consistency for reliability were checked before data collection. The study sample consisted of (76) male and female athletes with physical and visual disabilities. These athletes were registered at the Jordanian Paralympic committee for 2020. The study sample was chosen intentionally. Results: The results of the study show that the level of big five personality factors among players of adapted team and individual sports were moderate. More specifically, conscientiousness and agreeableness factors were high, whereas extraversion, openness to experience and neuroticism were moderate. There were no significant differences in the big five personality factors between disabled players of team and individual sports (P > 0.05).  However, neuroticism factor was higher among athletes with less experience of practice compared to those with more experience (P < 0.05). Conclusions: The study recommends that each sports team have a psychologist. Moreover, psychological preparation plan should be adopted to overcome difficulties faced by players' disabilities.